The Effect of Thoroughbred Bloodline Proportion on the Running Speed of Indonesian Crossbred Racehorses - Muhammad Danang Eko Yulianto; Tety Hartatik; Tri Satya Mastuti Widi; Panjono Panjono (Faculty of Animal Science, Universitas Gadjah Mada, 2026)
This study investigated the relationship between Thoroughbred bloodline proportions and the running speeds of Indonesian crossbred racehorses, along with key influencing factors since Indonesia racehorse breeding was based on Thoroughbred crossbred scheme since 1975 era. Data were gathered from race profiles and performance records of Indonesian horse racing events from 2012 to 2023, enabling an analysis of trends in racehorse achievements during this period, with measurements obtained via stopwatches, race video recording, and photo finish documentation. Observed variables included horse performance across different ages, sexes, breeds, race distances, and running speeds. Differences among breeds, sex, age, and race distances were analyzed using factorial analysis of variance followed by Duncan’s multiple range test (p< 0.05), while Spearman’s correlation test assessed the relationship between variables. Results indicated breed composition among race participants as follows: 42.43% G4; 23.86% G3; 13.03% KPI, 6.20% local breeds, and 3.01% Thoroughbred (THB) Indonesia. The population was 52.57% males and 47.49% females. Local breeds had the smallest wither’s height (133.65 cm), whereas the THB Indonesia breed had the highest (165.4 cm). The KPI.5 breed exhibited the highest running speed (15.15 m/s or 54.54 km/h), while the local breed had the lowest (13.54 m/s or 48.74 km/h). The study conclude that race speed is significantly influenced by horse breed and race distance, with additional correlations between running speed, wither’s height, and race distance.